Constructing knowledge and ignorance in the social information worlds of young mothers. Issue 1 (24th October 2017) - Greyson, Devon; O'Brien, Heather; Shoveller, Jean
ABSTRACT: The socially constructed information worlds within which individuals live, work and play necessarily shape their information practices. One way in which this occurs is through the social construction of knowledge, expertise and ignorance, including which actors are considered to possess authoritative knowledge through administrative authority or lay expertise. Using Adele Clarke's situational mapping techniques, this paper examines the discursive construction of knowledge and ignorance in the information worlds of young mothers in the Greater Vancouver region of Canada. Data was collected via observations at school‐based Young Parent Programs and interviews with 37 young mothers over a 15‐month time period. Gendered and racialized young parent social worlds discursively constructed the "teen mom" as knowledgeable in matters of sexuality and technology and ignorant in matters of parenting and health. Further, certain forms of experiential expertise common to marginalized groups were sometimes constructed in such information worlds as forms of ignorance. Recognizing the diversity of knowledge and expertise among young mothers rather than perceiving them as unilaterally information poor may lead to improved information and support services for young parents.